Analisis Bunyi dan Bahasa Figuratif dalam Mantra Berpantang Bersalin Desa Talau Kecamatan Pangkalan Kuras Kabupaten Pelalawan - Putri, Lia Artika; Shomary, Sudirman (UIR Press, 2025)
The Malay mantra in Talau Village, Pangkalan Kuras District, Pelalawan Regency, which incorporates stylistic characteristics and the beauty of the language, serves as the inspiration for this study. These components include both figurative language and acoustic components. The study's issues are as follows: (1) How effective is Talau Village, Pangkalan Kuras District, Pelalawan Regency's abstention from childbearing mantra? (2) How does Talau Village, Pangkalan Kuras District, Pelalawan Regency's slogan of abstinence from childbirth use metaphorical language?. The aim of this research is to describe, analyze, and draw conclusions about the sound component of the abstinence from childbirth mantra in Talau Village, Pangkalan Kuras District, Pelalawan Regency, as well as the figurative language used in this mantra. This study mantra is based on the hypotheses of Pradopo (2012), Nurgiyantoro (2014), and other corroborating theories. The research's data are in the form of figurative language, which includes linking figures of speech (metonymy and synecdoche) and comparing figures of speech (metaphor, personification, allegory, and simile), as well as sound elements, which include rhyme, rhythm, tone, and atmosphere. This study takes a qualitative approach and employs a descriptive analytic method with a field research design. Techniques for gathering data include interviews, documenting, and recording. The results of this study can be concluded that there are stylistic elements in the mantra of abstaining from giving birth in Talau Village, Pangkalan Kuras District, namely the sound aspect in rhyme totaling 81 words, rhythm totaling 191 words, tone and atmosphere totaling 145 words and figurative language/figurative language in personification figures of speech totaling 1 data, synecdoche figures of speech totaling 1 data, and metaphor figures of speech totaling 4 data. Examples of sound aspects of rhyme at the end with an a-b-a-b pattern in the mantra of fresh flour after the burial of the placenta, in rhythm, it contains euphonic rhythm which when read quickly with low tone pressure in the mantra for a breech baby, in tone and atmosphere there is an atmosphere of self-confidence of the village midwife contained in the mantra of strengthening the baby's umbilical cord and an example of figurative language of metaphor in the sacred lime mantra.